2010
DOI: 10.1371/journal.pone.0014095
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Rejuvenation After Induced Pluripotency

Abstract: BackgroundAs stem cells of the early embryo mature and differentiate into all tissues, the mitochondrial complement undergoes dramatic functional improvement. Mitochondrial activity is low to minimize generation of DNA-damaging reactive oxygen species during pre-implantation development and increases following implantation and differentiation to meet higher metabolic demands. It has recently been reported that when the stem cell type known as induced pluripotent stem cells (IPSCs) are re-differentiated for sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
194
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(208 citation statements)
references
References 38 publications
14
194
0
Order By: Relevance
“…These mitochondrial changes also impacted the cellular bioenergetic profile, which shifted from OXPHOS to glycolysis upon reprogramming and returned to OXPHOS during subsequent differentiation [18,19]. Other groups confirmed these results and showed that mitochondria within human iPSCs exhibits low oxidative stress [20] and energetic rejuvenation [21]. Moreover, small molecules inducing metabolic switch toward glycolytic metabolism enhanced reprogramming efficiency [22].…”
Section: Introductionmentioning
confidence: 86%
“…These mitochondrial changes also impacted the cellular bioenergetic profile, which shifted from OXPHOS to glycolysis upon reprogramming and returned to OXPHOS during subsequent differentiation [18,19]. Other groups confirmed these results and showed that mitochondria within human iPSCs exhibits low oxidative stress [20] and energetic rejuvenation [21]. Moreover, small molecules inducing metabolic switch toward glycolytic metabolism enhanced reprogramming efficiency [22].…”
Section: Introductionmentioning
confidence: 86%
“…Interestingly, iPS cells not only express stem cell markers, but also stem cell characteristics including anaerobic metabolism, low reactive oxygen species generation and decrease in mitochondrial mass and number (Armstrong et al, 2010;Prigione et al, 2010;Suhr et al, 2010). It has been suggested that the decrease in mitochondrial numbers contributes to lower generation of superoxide ions in iPS cells as compared to their progenitors (Vessoni et al, 2012).…”
Section: Possible Role Of Autophagy In Ips Cell Generationmentioning
confidence: 99%
“…Recent studies have shown that iPSC-derived cells may also display functional improvements when compared to the parental cells from which these iPSC were originally reprogrammed, indicating that they can be a preferred source for autologous cell-based therapies. For example, fibroblasts differentiated from iPSC displayed improved functional features, such as extended replicative potential, increased mitochondrial function, 1,2 and wound reparative potential. 3 Acquisition of these features suggests that iPSC are rapidly becoming a renewable source for regenerative therapies of the oral mucosa.…”
Section: Scope and Significancementioning
confidence: 99%
“…4 There is intriguing evidence that iPSC reprogramming may improve cellular function upon iPSC differentiation to a fibroblast lineage. 1,3,5 In this light, the use of iPSC-derived fibroblasts may circumvent the limitations of existing sources of fibroblasts that are currently used for tissue repair. This suggests that it may soon be possible to leverage the biological potential of iPSC-derived cells to improve current strategies for oral mucosal wound healing.…”
Section: Translational Relevancementioning
confidence: 99%
See 1 more Smart Citation